Esophageal granular cell tumor and eosinophils: a multicenter experience - Deepti Reddi; Christropher Chandler; Diana Cardona; Michael Schild; Maria Westerhoff; Emily McMullen; Yutaka Tomizawa; Lani Clinton; Paul E. Swanson (BMC, 2021)
Abstract Background Esophageal granular cell tumor (eGCT) is rare, and the recent literature suggests a link between eosinophilic esophagitis (EoE) and eGCT. The aim of our study was to determine if EoE or other disorders associated with eosinophilia are consistently associated with eGCT. Methods We retrospectively searched pathology databases of three academic institutions from 1999 to 2018 for eGCTs. The archived slides and medical records were reviewed. Results From 294,855 esophagogastroduodenoscopy procedures, 45 patients (17 males and 28 females) with eGCTs were identified. The patients (30-73 years in age, median 50) had eGCT 0.2-2.0 cm in size (average 0.71). Thirteen had a history of gastroesophageal reflux disease, 5 had Barrett esophagus/goblet cell metaplasia and 1 had EoE. Thirty-four eGCTs had intralesional eosinophils (14 with peak > 10 eosinophils/400x hpf); of these, 21 also had eosinophils in lamina propria (9 with peak > 10 eosinophils/hpf). eGCT with atypical features (including nuclear enlargement and prominent nucleoli) were more likely to have increased eosinophils in non-epithelial compartments than those without atypia. Pleomorphism and spindled cells were seen in 3 eGCT cases (mean peak intralesional eosinophils: 43 per hpf); 2 of these had goblet cell metaplasia. We found no association between EoE and eGCT, p = 0.5966, (95% C.I. 0.0276, 6.5389, Fisher's exact test). Instead, most patients had gastroesophageal reflux disease or Barrett esophagus. Conclusion Eosinophilia, common in eGCT and adjacent stroma, likely drives atypical/reactive histologic features, but a pathogenic relationship between eosinophil rich inflammatory conditions and eGCT has not yet been established.